On the Tasks and Prospects of SCO Activities in the Future (Proceedings of the 10-th Session of SCO Forum) - A. Lukin; A. Ivanov (Международная аналитика)
Short review of all reports and most important speeches of the participants of the 10-th SCO Forum in Khanty-Mansiisk.